Metacognitive Emotional Modeling within the Hidden Curriculum of Islamic Early Childhood Education: A Collective Case Study from Indonesia - Herlina; Rahayu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Emotional regulation in early childhood is shaped not only through formal instruction but also through the implicit emotional scripts children encounter in daily classroom interactions. In Islamic early childhood education, these scripts are closely connected to Adab (manners), Akhlaq (morality), and Uswah Hasanah (prophetic role modeling), yet the cognitive processes through which teachers translate these moral ideals into observable pedagogical practice remain underexplored. This study examines how teachers’ metacognitive awareness and reflective practice shape emotional modeling within the hidden curriculum of Islamic preschools. Using a qualitative collective case study design, data were collected through classroom observations and semi-structured interviews with three purposively selected teachers from Islamic-oriented preschools representing different socio-economic settings in Makassar, Indonesia. The findings show that teachers’ metacognitive monitoring enables them to pause, regulate verbal responses, repair emotional tension, and make emotional recovery visible to children. Reflective practice strengthens this process by helping teachers evaluate classroom interactions and adjust emotional communication across different situations. The study identifies metacognitive emotional modeling as a pedagogical mechanism through which Uswah Hasanah becomes an observable and reproducible classroom practice. Rather than treating Islamic moral pedagogy as an abstract theological ideal, the findings show how culturally grounded emotional modeling can support children’s emerging self-regulation. The study offers a globally relevant framework for analyzing teacher emotional competence in culturally responsive and faith-based early childhood education contexts.